(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
In the article the specificity of creative works of one of the leading poets of Ukrainian literature late XIX – early XX centuries Alexander Oles (Kandyba). The author identifies the leading features of artistic content and implementation of the concept of love in lyrical poetry artist. The main focus is on analyzing figures lyrical and collective image of women.